Measuring hotel service quality based on fuzzy-SERVQUAL and importance performance analysis - Tri Handayani (Universitas Negeri Padang, 2021)
This study aims to prove and analyze the effect of service quality at Grand Inna Muara Padang Hotel by using Fuzzy-SERQUAL Analysis and Importance Performance Analysis (IPA). In this study, 57 customers of Grand Inna Muara Padang Hotel were used who were selected using purposive sampling. Based on the results of Fuzzy analysis, it can be seen that the average rank value of the real values ​​obtained ranges from three so that it can be concluded that the satisfaction felt by customers is quite high in using the services of the Grand Inna Muara Hotel. the performance felt by the customers of Grand Inna Muara Padang Hotel so that satisfaction can be realized in the customer.